Experimental characterization of quaternary blended mortar exposed to marine environment using mechanical strength, corrosion resistance and chemical composition. (October 2021) - Srinivas, Dodda; Ramagiri, Kruthi Kiran; Kar, Arkamitra; Adak, Dibyendu; Noroozinejad Farsangi, Ehsan; Dutta, Subhrajit
Abstract: The durability of concrete is significantly influenced by its binder composition, especially in the presence of aggressive chemical environment. This paper represents a study on the strength, durability, and corrosion resistance of quaternary blended mortar made with Portland pozzolana cement (PPC), ground granulated blast furnace slag (GGBS) and rice husk ash (RHA) exposed to marine environment. Binary blended concrete mix using GGBS and RHA as partial replacement for cement is already well established. Previous research reports several shortcomings in using binary blended and ternary mix including low initial strength and increasing shrinkage strains with increasing percentages of GGBS, silica fume and RHA as partial substitutes for cement. Hence, this study is focused on overcoming the limitations of binary and ternary blended mixes by implementing a quaternary blended mix using GGBS and RHA to partially replace cement. This quaternary blended cementitious system is optimized based on its mortar compressive strength, determined by varying the percentages of GGBS and RHA as substitute for cement. These optimized quaternary mortar specimens are moist-cured for 28 days and then exposed to an artificially prepared marine environment for 180 days. The optimized quaternary blended mortar specimens show improved mechanical strengths, both compressive and flexural. These specimens also exhibit enhanced resistance to chloride penetration, corrosion, and water absorption compared to the control mix after 28 days of water curing. A quaternary blended mortar mix prepared with 70% PPC, 20% GGBS, and 10% RHA exhibits the maximum mechanical strength, resistance to chloride penetration, and corrosion, mass loss and water absorption upon exposure to marine environment up to a period of 180 days. Mineralogical analyses using X-ray diffraction (XRD), chemical bond analyses using Fourier Transform Infra-Red (FTIR) spectroscopy, and microanalyses using scanning electron microscopy (SEM) in conjunction with energy dispersive X-ray spectroscopy (EDS) are implemented to determine the effects of marine environment exposure on the different mixes. The findings are then used to corroborate the observations from the specimen scale mechanical and chemical characterizations. Highlights: The present study determines the detailed mechanical strength, long term peromance, minerological and microstructural analysis of blended mortar mix before and after exposure to the marine environment. The superior blended mortar mix with 70% Portland Pozzolana Cement, 20% GGBS and 10% RHA exhibited improved strength and durability compare to all other mixes before and after exposed to marine environment. The presence of a suitable amount of mineral admixture in the cement mix produces secondary C–S–H, M-S-H, and gypsum which block the pores present in the cement matrix and densifies the microstructure.